24. CURRENT STATUS OF TEACHING AND LEARNING INFECTION PREVENTION AND CONTROL AT HAI DUONG MEDICAL TECHNICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of teaching and learning infection prevention and control among nursing students at Hai Duong Medical Technical University.Methods:A cross-sectional study was conducted on 354 second-, third-, and fourth-year nursing students at Hai Duong Medical Technical University from October 2022 to October 2023 using a structured questionnaire.Results:The study population consisted of 15% male and 85% female students, with an average age of 20.03 ± 0.90 years. A total of 91% of students stated that the infection prevention and control (IPC) course helped them gain deeper professional knowledge and develop certain competencies. Over 80% of students agreed with the content and teaching methods of the course. However, the proportion of students who were not confident in practicing certain skills remained high: 26% in waste classification, 23.4% in safe collection and transportation of medical waste, and 20.1% in environmental surface cleaning. About 96.9% of students expressed the desire to borrow the practice room for self-study. More than 20% of students reported a lack of equipment for practicing sterilization–disinfection, linen management, and environmental hygiene, and suggested that the practice room should be designed to resemble clinical settings.Conclusion: The integration of infection prevention and control content into the nursing curriculum has demonstrated initial effectiveness in fostering students’ knowledge, clinical skills, and professional attitudes. However, there is a need to enhance the availability of equipment, increase support from lecturers, and redesign the practice rooms to improve training effectiveness and strengthen students' practical competencies in real-world clinical settings.
Keywords: Infection prevention and control; nursing students